The Efficacy of Functional Endoscopic Sinus Surgery Combined With Triamcinolone Acetonide Aqueous Nasal Spray for the Treatment of Chronic Rhinosinusitis - Hao, Zhongping; Gu, Huaiyu; Li, Wen (Frontiers in Surgery, 2022)
Objective: We aimed to investigate the efficacy of functional endoscopic sinus surgery (FESS) combined with triamcinolone acetonide aqueous nasal spray (TAA AQ) for the treatment of chronic rhinosinusitis. Methods: From December 2019 to June 2021, 109 patients with chronic rhinosinusitis were classified into a control group (n = 50) and an experimental group (n = 59) according to the method of treatment. Subjects in the control group were treated with FESS while those in the experimental group were treated with FESS + TAA AQ. We then compared clinical indices, total effective rate, and the clinical symptoms of patients between the two groups. The pre- and postoperative serum levels of inflammatory cytokines were also determined. Before and 12 months after surgery, we analyzed the recovery of nasal mucosa, olfactory function, and mucociliary transport rate of each patient. Postoperative complications were observed and recorded and the quality-of-life 12 months after surgery was ascertained. Results: Clinical indices and total effective rate were higher in the experimental group. After treatment, the VAS score and serum levels of inflammatory cytokines in the two groups both decreased, although the experimental group had lower VAS scores and inflammatory cytokine levels. Six months after treatment, olfactory function, and the recovery of nasal mucosa were improved, MTR had increased, and the total incidence of complications had reduced in the experimental group when compared with the control group. No significant difference was found between the two groups in terms of quality-of-life (P > 0.05). Conclusion: The combination of FESS and TAA AQ exerted a certain therapeutic effect on chronic rhinosinusitis.